A Facile Fabrication of Silver-Coated Copper Nanowires by Galvanic Replacement. (31st July 2016) - He, Xin; He, Ruihui; Lan, Qiuming; Duan, Feng; Xiao, Jundong; Song, Mingxia; Zhang, Mei; Chen, Yeqing; Li, Yang
Abstract : We demonstrated a general strategy to fabricate silver-coated copper nanowires by a galvanic replacement, which is guided by the chemical principle that metal ions (silver ions) with a relatively high reduction potential can galvanically etch nanostructure made from a less metal (copper). Well-dispersed and high-yielded copper nanowires were initially synthesized and then introduced into silver-ammonia solution for the growth of silver nanocrystals on the nanowire surfaces under vigorous oscillation. The results of X-ray diffraction, scanning electron microscope, and transmission electron microscope revealed that the silver nanocrystals were uniformly distributed on the copper nanowire surfaces to form Cu-Ag heterostructures. The concentration of silver-ammonia solution and the time of replacement reaction determine the size and density of the silver nanocrystals. Our investigation might pave the way to the synthesis of other bimetallic nanostructures via a facile, fast, and economical route.